Implementation of drive mechanism to control worktable motion in planer machine tool. (2022) - Chelliah, Sivakumar; Geetha Selvarani, A.; Yogaraj, D.; Tiwari, Piyush; Vishwakarma, Bhaskar; Sharma, Abhishek
Abstract: Recent technological development circumstances, the small changes and captivity of any sectors may prove to a commendable fact. In the area of manufacturing its value adds to the core of obtaining a successful product and even the safety process in addition. Whatever be the factors and parameters it should be considered, even its impact is not so effective on the machine or the operators performing. In the planer machine, the reciprocating motion is high, the operators (students) cannot operate it conveniently. In our laboratory, the motor which is being used as 3HP motor with the 1440 rpm. Replacing of motor is possible to vary (fluctuation of) the power, but while considering on the basis of cost it is more. It cost about 15000/- and power consumption is more. The slight variation or changes in the planer machine setup fetches some safety to the operators especially the students who performing some machining process in the planer machine. Reduction of the rpm is by reducing the motor rpm from 288 (before drive implementation) to 172 (after drive implementation) by drive mechanism method. This is to control the reciprocating motion of the table and at the same time we are not considering the process parameters during the machining process.